The problems in reading comprehension of Chinese passages by non-Chinese Malaysian undergraduates - Wong, Ling Yann (Nanyang Technological University and Singapore Centre for Chinese Language Publisher, 2014)
This study investigates the correction between the use of Malay alphabets for the romanization of Chinese characters by non-Chinese learners and their test results in Chinese reading comprehension. The subjects involved are Malay undergraduates from Universiti Putra Malaysia who learn Chinese as a foreign language. The study examines whether the mother tongue of this group of Malay undergraduates affect their performance in Chinese passages comprehension. There are two main findings: (1) The cognitive thinking of the subjects was affected by their mother tongue. To comprehend a Chinese passage, they needed to go through an intermediate step by romanizing Chinese characters based on the sound system of the alphabets in Malay, their mother tongue. They would then proceed to use Malay to translate the meanings of Chinese comprehension test of the subjects. The increase in the percentage of romanizing Chinese characters by the Malay undergraduates did not result in a corresponding increase in the percentage of scores for their Chinese comprehension test.